HUBUNGAN KADAR ZINK SERUM DENGAN FUNGSI KOGNITIF PADA LANJUT USIA - Prabaningrum Widyasmoro Prasetyanti,* Hexanto Muhartomo,* Maria Immaculata Widiastuti* (NEURONA, 2019)
BACKGROUND DIETARY FOOD INTAKE CAN INFLUENCE BRAIN FUNCTION INCLUDING ZINC THAT HAS ITS HIGHER LEVEL AT HIPPOCAMPUS AND AMYGDALA THE MOST VULNERABLE AGE GROUP THAT WERE EXPOSED TO ZINC DEFICIENCY IS ELDERLY PEOPLE 60 YEARS ZINC DEFICIENCY CAN LEAD TO COGNITIVE DYSFUNCTION SO EARLY DETECTION IS REQUIRED